The fraternity and education for peace: pedagogical possibilities - Larissa Cerignoni Benites; Samuel Souza Neto; Marina Cyrino; Mariane Gimenes Costa; Julia Jacomini Costa (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
In concern with the process of training the look of this study in question turned to the process of continuing education, in particular an extension course called "Escola de Educadores" which has the theme of fraternity and understanding of education for peace as pedagogical possibilities. Thus, the research aimed to clarify the proposal and determine the course of material production and the ratio of participants to the subject in question. This is a study which has the qualitative analysis approach your point of reference, emphasizing the exploratory study. As a result indicates that the course has a structure consistent with its objectives and presents pedagogical actions planned and systematic, which has theoretical and / or practical nature that are not included in the curriculum structure of the regular courses at the undergraduate or post and make the "rethink teaching "the teacher. On the production of material, it was noted the incorporation of themes worked for the course in reading the final papers and innovative initiatives in stages. In conclusion character means that the extension course, presents itself as a training opportunity, but also a universe of new experiences and challenges.